Drivers of blue economy in Asia and Pacific Island countries: An empirical investigation of tourism and fisheries sectors - Poulomi Bhattacharya; Aruna Kumar Dash (Asian Development Bank Institute (ADBI), 2020)
This study examines the determinants of blue economy activities, namely tourism and fisheries, in 21 Asia and Pacific island countries during the period 1996 to 2016. Using a panel data model, it was found that the size of the blue economy positively depends on the gross fixed capital formation and access to electricity in Asia and Pacific island countries. We find that the size of the blue economy has responded positively to sustainable ocean management policies. Hence, our findings support the need for, and effectiveness of, the implementation of sustainable ocean governance policies in the Asia and Pacific island region, which can further strengthen the growth of these island countries.
Keywords: Q22; O56; C33; 330; blue economy; tourism; fisheries; sustainability; island countries; panel data model